Penerapan Slow Deep Breathing Terhadap Masalah Keperawatan Ketidakefektifan Manajemen Kesehatan Keluarga Pada Lansia Hipertensi - Bakri, Zakiah Kamila; Ezalina; Saputra, Candra; H, Afrida Sriyani (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: Hypertension is the number one cause of death globally each year and is a common condition treated at primary healthcare facilities. Ineffective family health management is a barrier to making lifestyle changes that could improve health status. This ineffectiveness can lead to complications or further consequences, making the presence of a family caregiver essential. Non-pharmacological treatments that must be implemented by individuals with hypertension include controlling food and sodium intake, losing weight, limiting alcohol and tobacco use, and engaging in physical exercise and relaxation. One relaxation technique that can be used by individuals with primary hypertension is slow deep breathing. The purpose of this study was to explain Family Nursing Care with the Application of Slow Deep Breathing to the Nursing Problem of Ineffectiveness of Family Health Management in Elderly Hypertension in RW 02, Tuah Negeri Village, Tenayan Raya District, Pekanbaru City. The method used in implementing nursing interventions is the provision of Slow Deep Breathing therapy for hypertension sufferers. This study was conducted from November 25-29, 2024. The implementation of Slow Deep Breathing therapy was carried out for 3 days, 6-10 times for 5 minutes. The results of this case study after 3 days of subjects applying Slow Deep Breathing therapy showed that on average after being given there was a significant difference between the decrease in blood pressure before and after being given Slow Deep Breathing therapy in elderly Hypertension. Keywords: Slow Deep Breathing, Hypertension, Ineffective Family Health Managemen